THE SACREDNESS OF COMMUNICATION IN THE NGASUH GUMI TRADITION OF THE NORTH LOMBOK: AN ETHNOGRAPHIC ANALYSIS - Sarjono; Kadri; Mohammad Fakhri (KOMUNIKE: Jurnal Komunikasi Penyiaran Islam, 2023)
The criticality of Ngasuh Gumi ceremonial communication practices for the Tanjung people in North Lombok. The purpose of this study is to comprehend the significance and steps of the Ngasuh Gumi ceremonial procedure. An ethnographic design is a component of the qualitative research methodology. The findings demonstrated the significance of ritual communication in the Ngasuh Gumi tradition for the local population. Ritual communication is symbolic rather than information-focused. Confirmation, breaking, notification, matur penguningan, and burial of the buffalo head are among the processes. The Ngasuh Gumi ritual serves as a way of warding off danger in human life as well as a symbol of the "tri-relation" of human life, upholding and caring for the preservation of nature and ecology.